Answer:
The answer to your question is y = -2x + 11
Step-by-step explanation:
A (1, 9)
B (3, 5)
- Find the slope



m = - 2
- Find the line equation
y - y1 = m (x - x1)
y - 5 = -2(x - 3)
y - 5 = -2x + 6
y = -2x + 6 + 5
y = -2x + 11
There are no pictures I see you can text me on insta if you need help original_loredo
Complementary angles = 90
x+y =90
y=x+24
substitute this in to the equation
x+x+24=90
2x+24=90
subtract 24 from each side
2x = 66
divide by 2
x=33
y = 33+24
y=57
Answer: 33, 57
Answer:
D
Step-by-step explanation:
The correct inequality is not listed
Answer:
C. y = x^2 -10x +26
Step-by-step explanation:
The translated function is ...
g(x) = f(x - right) + up
g(x) = f(x -5) +1
g(x) = (x -5)^2 +1
g(x) = x^2 -10x +26
In "y =" form, this is ...
y = x^2 -10x +26 . . . . matches choice C